Beetroot Powder (Beta vulgaris L.) Decrease Oxidative Stress by Reducing of Malondialdehyde (MDA) Levels in Hyperuricemia - Wulandari, Anggraini; Dirgahayu, Paramasari; Wiboworini, Budiyanti (Journal of International Conference Proceedings, 2021)
Introduction: Hyperuricemia is a metabolic disease associated with lifestyle habits, age, sex, and inherited factors. High uric acid levels in a hyperuricemia state cause oxidative stress that can lead to increased malondialdehyde (MDA) levels. Beetroot powder has the potential as a functional food rich in antioxidants that can reduce MDA levels. This study aims to determine the beetroot powder effect on MDA level reduction in hyperuricemia rat models. Methods: This research was an experimental study with fifteen hyperuricemia rats were divided into three groups by randomized pre-post control group design. They were divided into three groups: P1 were healthy rats + standard feed (comfeed), P2 were hyperuricemia rat models + standard feed (comfeed) and P3 were hyperuricemia rat models + beetroot powder 3,12 g/kg/bw for 14 days. The MDA level examinations were conducted on day 0 and day 14. Results: After 14 days of treatment, the P3 group has a significant decrease in MDA levels compared to day 0 (p = 0.042). Groups P1 and P2 have a significant increase in MDA levels (p = 0.043). MDA levels between groups were significantly different (p = 0.002) on day 14. Conclusion: Giving beetroot powder for 14 days with dose 3,12 g/kg/bw for 14 days significantly reduced MDA levels in hyperuricemia.